On the Estimation of Bid-Ask Spreads: Theory and Evidence - Choi, J. Y.; Salandro, Dan; Shastri, Kuldeep (Journal of Financial and Quantitative Analysis, 1988)
This paper extends the Roll model for implicit bid-ask spreads by incorporating the possibility of serial correlation in transaction type. The validity of this formula is examined using intra-day transactions and bid-ask spread data for options traded on the Chicago Board Options Exchange. The results indicate that the model derived here closely estimates the effective bid-ask spread in that it explains more than 80 percent of the crosssectional differences in announced bid-ask spreads.